Isolation, proliferation and characterization of endometrial canine stem cells. (7th December 2016) - De Cesaris, V; Grolli, S; Bresciani, C; Conti, V; Basini, G; Parmigiani, E; Bigliardi, E
Contents: In the last decade, progenitor cells isolated from dissociated endometrial tissue have been the subject of many studies in several animal species. Recently, endometrial cells showing characteristics of mesenchymal stem cells (MSC) have been demonstrated in human, pig and cow uterine tissue samples. The aim of this study was the isolation and characterization of stromal cells from the endometrium of healthy bitches, a tissue that after elective surgery is routinely discarded. Multipotent stromal cells could be isolated from all bitches enrolled in the study ( n  = 7). The multipotency of cells was demonstrated by their capacity to differentiate into adipocytic, osteocytic and chondrocytic lineages. Clonogenicity and cell proliferation ability were also tested. Furthermore, gene expression analysis by RT‐PCR was used to compare the expression of a set of genes (CD44, CD29, CD34, CD45, CD90, CD13, CD133, CD73, CD31 CD105, Oct4) with adipose tissue‐derived MSC. Stromal cells isolated from uterine endometrium showed similar morphology, ability of subculture and plasticity, and also expressed a panel of genes comparable with adipose tissue‐derived MSC. These data suggest that endometrial stromal cells fulfil the basic criteria proposed by the "Mesenchymal and Tissue Stem Cell Committee of the International Society for Cellular Therapy" for the identification of mesenchymal stem cells. Although endometrial mesenchymal stem cells (EnMSC) showed a lower replicative ability in comparison with adipose tissue‐derived MSC, they could be considered a cell therapeutic agent alternative to adipose tissue or bone marrow‐derived MSC in dog.